Cntn6 deficiency impairs allocentric navigation in mice. Issue 6 (20th April 2018) - Mu, Di; Xu, Yiliang; Zhao, Tian; Watanabe, Kazutada; Xiao, Zhi‐Cheng; Ye, Haihong
Abstract: Introduction: CNTN6 is an immunoglobulin domain‐containing cell adhesion molecule that belongs to the contactin family. It is involved in the development of the nervous system. We aim to determine the effect of Cntn6 deficiency on the allocentric navigation in mice. Methods: We recorded the travel distance and escape time of wild‐type and Cntn6 mutant male and female mice in the Morris water maze task according to the protocol. Results: There was hardly any Cntn6 expression in the hippocampus of postnatal day 0 (P0) mice, while obvious Cntn6 expression was present in the hippocampal CA1 region of the P7 mice. During the acquisition period of Morris water maze task (Day 1 to 4), Cntn6 −/− male mice failed to shorten the escape time to reach platform on the third day, while the travel distance to platform was not significantly different. There was no significant difference in both escape time and travel distance to the platform among all female subjects. In the probe trial test (Day 5), spatial memory of the female mutant mice was mildly affected, while Cntn6 −/− male mice were normal. In the spatial relearning test (Day 7 to 10), Cntn6 −/− male mice showed no difference in escape time to the platform compared to the wild‐type male mice, while Cntn6 deficient female mice required shorter escape time to travel to the platform on day 7, day 8, and day 10. Conclusions: Cntn6 is expressed in the developing hippocampus in mice. Cntn6 deficiency affects spatial learning and memory, indicating that Cntn6 plays a role in the development of hippocampus and affects allocentric navigation of the animals. Abstract : Cntn6 is expressed in the developing hippocampus in mice. Cntn6 deficiency affects spatial learning of male mice. Cntn6 deficiency affects the spatial memory of female mice, while improves spatial relearning.